(untitled) (International Conference on Computers in Education, 2020)
This study investigated the stag and hare hunting behaviors of students in a computer- supported collaborative learning environment (CSCL). Our initial findings suggest that these behaviors do exist in a CSCL and that these behaviors have distinct characteristics. These behaviors are primarily driven by the personality traits of the students. Mobile CSCL will be improved based on the initial findings of the study. Future research directions and challenges are also discussed in this paper.